Use of Nepeta clarkei extracts for controlling honey bee pathogenic bacteria and mosquito larvae. Issue 1 (1st January 2018) - Anjum, Syed Ishtiaq; Shah, Ayesha Haleem; El-shakh, Ahmed S.A.; Ullah, Imran; Ullah, Amjad; Khan, Asifullah; Ali, Muhammad; Khan, Abdul Azeez; Khan, Adnan
ABSTRACT: Honeybee ( Apis mellifera ) population is going down across the globe due to honeybee pathogens. This greatly influences the bee-associated commercial food products production. Likewise, mosquitoes are prominent vector responsible for spreading life-threatening human diseases, including malaria and dengue. The plant-based insecticides are a better substitute to the recent control practices of honeybee pathogenic bacteria and mosquito. Here, we performed in vitro screening of Nepeta clarkei Hook. f. (Labiatae) aqueous extracts against three honey bee gut bacterial isolates including Paenibacillus larvae an infamous honeybee bacterial pathogen. The inhibitory zone was produced in the range of 6–14 mm diameters against three honey bee bacterial isolates . Likewise, fourth instars larvae of Culex (Diptera/Culicidae) were also subjected to check the possible larvicidal efficacy of N. clarkei . A normal media supplemented with N. clarkei in different concentrations (0.025% 0.05%, 0.1%, 0.15%, and 0.2%) affected the growth of larvae significantly. The lethal concentration at which 50% of larvae failed to become pupate was found to be 0.1% after 24 h of exposure. Considerable reductions in larval growth and pupal development of mosquito suggested that this plant should be utilized in mosquito control programmes.